Leakage monitoring research and design for natural gas pipelines based on dynamic pressure waves. (February 2017) - Liu, Cuiwei; Li, Yuxing; Fang, Liping; Han, Jinke; Xu, Minghai
Graphical abstract: Highlights: New method based on amplitude attenuation model of dynamic pressure wave is studied. All leakages can be detected by proposed methods based on dynamic pressure waves. Largest location error is 0.054% for new method and −0.780% for traditional method. Abstract: Many types of gases, such as natural gas, hydrogen, and so on, are transported via pipelines using a chemical process, though leakages in these pipelines create waste and pose hazards and risks to industries, the environment and people. To monitor gas pipelines, a new leak detection and location method based on the amplitude attenuation model of dynamic pressure waves was designed and researched by experiments, compared with traditional method based on the propagation velocity and time differences as determined by the waveforms of the upstream and downstream signals. Both methods are achieved based on the propagation law of the dynamic pressure waves in the fluid flow. First, the fundamentals of the newly proposed method are clarified by considering the influence of gas flow on the waves. The experiments are then conducted in gas pipelines with 42 mm internal diameters. Finally, the results of the experiments are discussed and analyzed. The results indicate that all leakages can be detected by both methods but that the largest location error of the traditional method is −0.780%, whereas the largest location errors with respect to the new method are 0.054% with the experimental attenuation coefficients and 2.055% with the theoretical attenuation coefficients. It is further determined that the influence of the gas flow effects cannot be ignored by either method. Accordingly, the conclusions drawn suggest that the proposed methods can be applied to monitor gas pipelines.